Effect of Abiotic Stresses on natural enemies of crop pests and mechanism of tolerance to these stresses - Jalali, S. K. (Indian Farming, 2015)
The NBAII alongwith NAIP undertook research to find out efficient strains of natural enemies of crop pests and to develops effective biopesticides thereof. From Trichogramma, best isolates were selected for insecticide and temperature tolerance studies. In Chrysoperla best isolates were selected for insecticide tolerance studies, different bacterial and yeast endosymbionts characterization etc. A total of 47 stress tolerance Pseudomonas isolates were obtained out of 230 isolates.